2016
DOI: 10.1007/s11010-016-2889-5
|View full text |Cite
|
Sign up to set email alerts
|

WT1 and NPHS2 gene mutation analysis and clinical management of steroid-resistant nephrotic syndrome

Abstract: Nephrotic syndrome (NS) is a kidney disease predominantly present in children with idiopathic condition; final stage of the disease progresses into end-stage renal disease. Generally, NS is treated using standard steroid therapy, however; most of the children are steroid sensitive and about 15-20% are non-responders (SRNS). Non-responsiveness of these children would be a risk with the possibility of mutational changes in podocyte genes (NPHS1, NPHS2, WT1, PLCE1). The mutation in podocyte genes is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…In their study, APOL1 variants were not associated with NS, but the NPHS2 V260E allele was specifically associated with SRNS (with FSGS) in black children; 8 were homozygous for the variant (OR 21; 95% CI, 2.8–960) and no heterozygotes were observed. The NPHS2 V260E variant alters the podocin protein and prevents the movement of the protein to the plasma membrane, affecting the structural integrity of the slit diaphragm 21 . This variant was absent in the Indian children (cases and controls) and absent in all black children with SSNS.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, APOL1 variants were not associated with NS, but the NPHS2 V260E allele was specifically associated with SRNS (with FSGS) in black children; 8 were homozygous for the variant (OR 21; 95% CI, 2.8–960) and no heterozygotes were observed. The NPHS2 V260E variant alters the podocin protein and prevents the movement of the protein to the plasma membrane, affecting the structural integrity of the slit diaphragm 21 . This variant was absent in the Indian children (cases and controls) and absent in all black children with SSNS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a novel intriguing co-expression module (the Yellow module) was also detected in this study, which contained genes involved in ‘glomerulus development’, ‘kidney development’ and ‘multicellular organismal development’ GO terms [e.g. NPHS1 (35), NPHS2 (36), WT1 (37), podocalyxin-like and PLCE1]. Since the Yellow module mainly contained genes downregulated in patients with CKD and was negatively correlated with CKD clinical traits; these results indicated that the renal parenchyma may be damaged in CKD and the corresponding repair mechanisms may be suppressed.…”
Section: Discussionmentioning
confidence: 61%
“…Nephrotic syndrome is a disease with a complicated pathogenesis caused by heredity, infection and other factors, in which the immune microenvironment is often out of balance (13,14). Primary nephrotic syndrome is nephrotic syndrome without definite cause.…”
Section: Discussionmentioning
confidence: 99%